Architectures of intergenerational justice: Human dignity, international law, and duties to future generations. Issue 2 (2nd April 2016) - Riley, Stephen
ABSTRACT: This article draws attention to the constitutive requirements of intergenerational justice and exposes the limitations of regulative arguments based on international human rights law. Intergenerational justice demands constraining the regulative freedom of the international community, and it is tempting to assume that adequate constraints are already contained within existing treaties including international human rights treaties. In fact, intergenerational justice demands bespoke constitutional norms at the international level, and it demands entrenching constitutional norms. International human rights law per se implies neither of these constitutive propositions and both are problematic in light of the present structure of international law. Nevertheless, a combination of arguments concerning intergenerational justice and the systemic implications of human dignity yield a more constitutive account of human rights and therefore an internal critique of the overall architecture of international law.